IMPLEMENTASI KEBIJAKAN TRANSPARANSI KEUANGAN DI DAERAH - Edah Jubaedah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
The concept of transparency in government finance has been established during recent decades as an instrument in the fight against organizational and individual irregularities such as corruption, fraud, and financial scandals as well as promoting good governance in such organizations as local government bodies. The laws governing access to the financial information held by the local government authorities are mainly aimed at increasing the transparency of governmentalbudget. However in practice, it seems that local government organizations often remain reluctant to freely and voluntarily reveal their financial information. Local governments still cope with several barriers in implementing financial tranparencypolicy.